PENGARUH MARKETING MIX TERHADAP MINAT PASIEN MENGUNAKAN JASA LAYANAN KESEHATAN PADA RUMAH SAKIT LANCANG KUNING PEKANBARU - Hasda Wati; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted at Hospital Lancang Kuning Pekanbaru. This study aims to determine how the influence of the Marketing Mix (Product, Price, Promotion, Location, People, Physical Evidence, customer service) to the Patient Interests (Awareness, Knowledge, preferences, options, Confidence, Purchasing) in Hospitals Lancang Kuning Pekanbaru.The problem in this research is the decline in the number of outpatient and inpatient in hospital Lancang Kuning pekanbaru so that the target does not correspond to what was targeted by the company.The population in this study were patients seeking treatment at the Hospital Lancang Kuning Pekanbaru. With 100 samples, sampling using the formula slovin. The data collection of primary data research, with questionnaires as an instrument of research and secondary data from company archives, data analysis used is by using simple linear regression, test of determination and t test with SPSS. From the results of data analysis include validity, reliability, and simple linear regression, t-test research results show the calculation of the t (14.058)> t table (1.984) and Sig. (0.000) <0,05.Artinya variable significant effect Marketing Mix to the patient's interest.Keywords: Marketing Mix, Patient Interests